An Italian dinosaur Lagerstätte reveals the tempo and mode of hadrosauriform body size evolution - Alfio Alessandro Chiarenza; Matteo Fabbri; Lorenzo Consorti; Marco Muscioni; David C. Evans; Juan L. Cantalapiedra; Federico Fanti (Scientific Reports, 2021)
Abstract During the latest Cretaceous, the European Archipelago was characterized by highly fragmented landmasses hosting putative dwarfed, insular dinosaurs, claimed as fossil evidence of the “island rule”. The Villaggio del Pescatore quarry (north-eastern Italy) stands as the most informative locality within the palaeo-Mediterranean region and represents the first, multi-individual Konservat-Lagerstätte type dinosaur-bearing locality in Italy. The site is here critically re-evaluated as early Campanian in age, thus preceding the final fragmentation stages of the European Archipelago, including all other European localities preserving hypothesized dwarfed taxa. New skeletal remains allowed osteohistological analyses on the hadrosauroid Tethyshadros insularis indicating subadult features in the type specimen whereas a second, herein newly described, larger individual is likely somatically mature. A phylogenetic comparative framework places the body-size of T. insularis in range with other non-hadrosaurid Eurasian hadrosauroids, rejecting any significant evolutionary trend towards miniaturisation in this clade, confuting its ‘pygmy’ status, and providing unmatched data to infer environmentally-driven body-size trends in Mesozoic dinosaurs.